Self-care practice and associated factors among postpartum mothers at Karat town, Konso zone, southern, Ethiopia: 2022 - Gebino Aylate Tengo; Samuel Abdu Aliyu; Enatfenta Sewmehone Endalew; Tilahun Nigusie Adafirie (BMC Pregnancy and Childbirth)
Abstract Background Every day, at least 700 women die from complications related to pregnancy, childbirth, and the first 42 days of postpartum period. One of the contributing elements to these issues is a lack of focus on self-care practices during the postpartum period. Thus, understanding the relationship between self-care practices and maternal health is crucial for saving mothers’ and babies’ lives. Therefore, this study was aimed to assess level of postpartum self-care practice and associated factors among mothers at Karat Town, Konso Zone, Southern, Ethiopia, 2022. Methods A community-based cross-sectional study was conducted on postpartum mothers who gave birth in the last six weeks in Karat Town from August 1 to September 15, 2022. The systematic random sampling was used to select 419 study participants. Data was collected using a pretest structured questionnaire through a face-to-face interview, entered and cleaned using EPI Info version 4.6, and exported to SPSS version 25 for analysis. Bivariable and multivariable logistic regression was employed to assess the association of the variables, and a P-value less than 0.05 was declared as statistically significant. Results Out of 419 mothers 140(33.4%) were good postpartum self-care practice. Having an antenatal care visit (AOR = 2.82; 95% CI = 1.394–5.709), institutional delivery (AOR = 2.42; 95% CI = 1.18–4.93), accompanying a husband in antenatal care (AOR = 2.41; 95% CI = 1.37–4.24), counseling by healthcare providers during home visits (AOR = 2.28; 95% CI = 1.24–4.19), and healthcare provider counseling at discharge (AOR = 3.25; 95%CI = 1.72–6.13), and knowledge of participants (AOR = 3.61;95%CI = 2.11–6.19) were factors significantly associated with postpartum self-care. Conclusion This study showed that self-care practices during postpartum period were low. Inspiring mothers to Attending ANC visits, institutional delivery services, accompanied husbands in antenatal care, strengthening provider’s health education at discharge and during home visit, and enhancing knowledge of participants are acceptable manner may improve the postpartum self-care practice.